Locke & key: heaven & earth ebook Heaven & earth. - Hill, Joe (Idea and Design Work, LLC, 2017)
This special deluxe release finally reprints the oft-requested and long-denied Eisner-winning one-shot, "Open the Moon!" Plus the other long-sold-out one-shot, "Grindhouse!" PLUS plus: the even more hard-to-find IDW 10th anniversary Locke & Key tale, "In the Can!" And additional covers, behind-the-scenes photos and more, all wrapped up in a beautiful 72-page hardcover package. Author: Joe Hill. Illustrator: Gabriel Rodriguez. Locke & Key script © 2019 Joe Hill; art © 2019 Idea and Design Works, LLC. All Rights Reserved.